Bartonella henselae in a dog with ear tip vasculitis. Issue 6 (14th October 2018) - Southern, Brittany L.; Neupane, Pradeep; Ericson, Marna E.; Dencklau, Jamie C.; Linder, Keith E.; Bradley, Julie M.; McKeon, Gabriel P.; Long, Charles T.; Breitschwerdt, Edward B.
Abstract : Background: Bartonella henselae, a Gram‐negative, zoonotic, alpha‐proteobacteria has been previously implicated in association with cutaneous vasoproliferative lesions (bacillary angiomatosis), nodular panniculitis and multifocal erythema (erythema multiforme) in dogs. Objective: Describe clinical, microbiological and histological lesions in a dog with ear margin vasculitis and B. henselae infection. Animals: A 12‐month‐old, specific pathogen‐free intact female beagle dog maintained in a vector‐free laboratory animal resource facility. Methods and materials: Bartonella and Rickettsia serological evaluation, Bartonella and Rickettsia PCR, Bartonella alpha‐proteobacteria growth medium (BAPGM) enrichment blood culture/PCR, histopathological investigation and confocal immunohistochemical evaluation. Results: Serological investigation (seroreversion) and PCR testing of aural tissue biopsies failed to support Rickettsia rickettsii as a cause of the aural vasculitis; however, B. henselae, genotype San Antonio 2 DNA was amplified and sequenced from both ear tip margins and from normal‐appearing abdominal skin. Seroconversion to B. henselae was documented retrospectively by IFA testing. Bartonella henselae organisms were visualized by confocal immunostaining within all three biopsies. Histopathology revealed small vessel necrotizing vasculitis and dermal necrosis. Bartonella henselae s eroreversion and complete resolution of skin lesions occurred in conjunction with administration of oral doxycycline and enrofloxacin for six weeks. Conclusions and Clinical Importance: Bartonella henselae is an emerging zoonotic pathogen that has been associated with leucocytoclastic vasculitis in humans and may have had a contributing or causative role in the development of the cutaneous aural margin vasculitis in this beagle. Abstract : Background – Bartonella henselae, a Gram‐negative, zoonotic, alpha‐proteobacteria has been previously implicated in association with cutaneous vasoproliferative lesions (bacillary angiomatosis), nodular panniculitis and multifocal erythema (erythema multiforme) in dogs.Objective – Describe clinical, microbiological and histological lesions in a dog with ear margin vasculitis and B. henselae infection.Conclusions and Clinical Importance – Bartonella henselae is an emerging zoonotic pathogen that has been associated with leucocytoclastic vasculitis in humans and may have had a contributing or causative role in the development of the cutaneous aural margin vasculitis in this beagle.